Development of the ODCRE Cooking Teaching-Learning Model Using QR Code to Promote Creativity of 5-Year-Old Young Children - Jai Kim, Hyoung; Hee Kim, Myung; Seo Song, Min (International Journal of Engineering and Technology, 2018)
Background/Objectives: The purpose of this study is to develop an ODCRE teaching-learning model of a cooking program using QR codes for young children in order to promote children’s creativity and to develop the program activity plans that reflect the ODCRE culinary teaching-learning model using QR code.            Methods/Statistical analysis: This study was developed through the following five stages: 1) diagnosing the necessity of the development of the culinary teaching-learning model, 2) understanding cooking classes, 3) establishing the basic direction of the culinary teaching-learning model, 4) developing the culinary teaching-learning model, and 5) completing the final culinary teaching-learning model.Findings: The teaching-learning model of a cooking program was developed as an ODCRE teaching-learning model through the following steps: 1) Creatively searching cooking ingredients (understanding the concept of creative cooking, exploring various cooking materials, and understanding of creativity knowledge), 2) cooking recipe (understanding various cooking methods using the selected cooking materials and recipe development using smart phone and iPad), 3) cooking practice (creative cooking and envisioning ideas – photographing and recording their creative cooking activities and cooking procedures) 4) representing the cooking (representing their activities after the program, saving it as an experience, and creating QR codes for their own cooking recipes), 5) evaluation (creative cooking activity evaluation, cleaning up, cuisine tasting, creating cookbook using QR code and family-involved activities).Improvements/Applications: The ODCRE culinary teaching-learning model using the QR code, developed in this study, was an effective model for improving the creativity of young children. In particular, the QR code adopted in the ODCRE culinary teaching-learning model developed in this study suggests that there is a great value in the field of young children education as a teaching and learning tool.
Keywords: cooking teaching-learning model; cooking program; young children; QR code; creativity.